126-134 Milk Street, ca. 1880 - Bellamy, William (Tufts Archival Research Center, 2005)
Street-level view northeast of (left to right) 126-134 Milk Street, located between Broad Street to the west-southwest and India Street to the east-northeast. Signage adorns the facades of the buildings, which face southeast towards Milk Street. Several men are captured in the photograph, including George and Horace Dodd, who are standing in the doorway of 130 Milk Street. Store at 130 Milk Street purchased by Timothy Dodd, 1850; Timothy Dodd, believed to be the oldest active merchant in the United States, died at age 95, 1876. Donated by Robert Severy. 7 1/16 x 4 5/16, 9 7/8 x 8 overall Photographs